Fundamental parameters of the Milky Way galaxy - Camarillo, Tia (Kansas State University, 2018)
Over three-quarters of observed galaxies are spiral galaxies, and of those spirals roughly two-thirds are barred. The Milky Way, a barred spiral galaxy, is naturally a great foundation to studying the structure of other barred spiral galaxies. Two important fundamental constants are used to describe the Milky Way, R₀ (the radial distance from the Sun to the Galactic center) and θ₀ (the Galactic rotational velocity at R₀). These two constants are also crucial for developing the rotation curve of the Galaxy, which helps to understand the mass distribution of the Galaxy and may be able to lend insight to the dark matter mass contribution. This work presents new, independently calculated values for R₀ and θ₀. The error distributions of a compilation of 28 (since 2011) independent measurements of R₀ are wider than a standard Gaussian and best fit by an n=4 Student's t probability density function. Given this non-Gaussianity, the results of our median statistics analysis, summarized as R₀ = 8.0 ± 0.3 kpc (2σ error), probably provides the most reliable estimate of R₀. The unsymmetrized value for R₀ is R₀ = 7.96+0.24-0.30 kpc (2σ error). A complete collection of 18 recent (since 2000) measurements of θ0 indicates a median statistics estimate of θ₀ = 220 ± 10 km/s ⁻¹ (2σ error) as the most reliable summary for most practical purposes, at R0 = 8.0 ± 0.3 kpc (2σ error). The resulting error distribution of this data set is only mildly non-Gaussian, much more so than that of R₀. These measurements use tracers that are believed to more accurately reflect the systematic rotation of the Milky Way. Unlike other recent compilations of R₀ and θ₀, our collections includes only independent measurements. This work concludes with a new set of Galactic constants (with 1σ error bars) of θ₀ = 222 ± 6 km s⁻¹, R₀ = 7.96 ± 0.17 kpc, and ω₀ = θ₀/ R₀ = 27.9 ± 1.0 km s⁻¹ kpc⁻¹ as probably the most reliable to date.
Keywords: Cosmology; Data Analysis